Adhesion of finishing material: Influence of timber species and coating layers / Mohamad Alif Mohd Yazied and Amran Shafie - Mohd Yazied, Mohamad Alif; Shafie, Amran (2012)
The adhesions of coating material (Nitrocellulose Lacquer) on Malaysian hardwood timbers were ascertained. The effects of different timber species such as Resak (Vatica spp) ( 655-1152 kg/m3) Chengal (Neobalanocarpus heimii) (915-980 kg/m3) Keruing (Dipterocarpus spp) (550-985 kg/m3) Meranti (Shorea spp) (385-755 kg/m3), Kedondong (Canarium spp) (495-975 kg/m3) and Rubberwood (Hevea brasiliensis) (560-640 kg/m3) with different number of undercoat layers (1, 2 and 3 layers) were determined. Conventional air spray gun was used for finishes application and air drying method to cure the coating. The American Society for Testing and Material (ASTM D3359:2009) standard testing and procedures were used. The result revealed that the lowest density of Malaysian hardwood timbers and the min number of under coating layer were strong enough for the adhesion of furniture finishes. Thus, it can be concluded that Meranti with 1 layer of under coating is better than other species to be used in furniture production.